Automating activation in Australia: a critical policy discourse analysis of the new employment services model - Papadopoulos, Angelika; O'Keeffe, Patrick (Critical policy studies, 2024)
This article critically analyses the policy discourse that accompanied the introduction of the 'New Employment Services Model' (NESM) into the Australian social security system. Critical policy discourse analysis of documents presenting reforms to employment services provision shows that the NESM embeds a logic of activation that construes job seekers both as passive units requiring external motivation (through 'employment support' and 'mutual obligation'), and as active agents responsible for their own situation. This contradictory logic results in inconsistencies between the espoused aims of the reforms and the experience of those subject to the policy mechanisms. Analysis of departmental outcomes data illustrates the inconsistent operational consequences of the conflation of 'targeted compliance' and 'support.' Due to the technological automation of activation processes, the real discursive innovation of the NESM is one of 'digital depoliticization,' whereby the moralizing assumptions that inform punitive activation are embedded and therefore concealed in the policy technology. The operational effect is to subordinate the achievement of employment to compliance with mutual obligation requirements as a structured aim of employment services provision.